2012
DOI: 10.1007/s10266-012-0088-8
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue resistance of rotary instruments manufactured using different nickel–titanium alloys: a comparative study

Abstract: The aim of this study was to investigate whether cyclic fatigue resistance is increased for Controlled Memory (CM) Nickel-Titanium (NiTi) instruments, compared to instruments produced using traditional NiTi and instruments produced using M-Wire alloy. Two groups of NiTi endodontic instruments consisting of identical instrument sizes (constant 0.06 taper and 0.25 tip diameter and constant 0.04 taper and 0.40 tip diameter) were tested: group A compared Hyflex™ CM, Vortex ™ and ProFile ™ size 25 and 0.06 taper an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 28 publications
5
58
0
12
Order By: Relevance
“…Our results showed that the HyFlex GPF instrument had the highest NCF. This finding might be attributed to the previously stated factors, and the most likely one is the differences in the manufacturing process (control memory wire) used to produce the HyFlex GPF instrument, which is in agreement with previous studies (13,(28)(29)(30). In the present study, all the tested instruments have square cross sections, with the exception of the G-Files.…”
Section: Discussionsupporting
confidence: 94%
“…Our results showed that the HyFlex GPF instrument had the highest NCF. This finding might be attributed to the previously stated factors, and the most likely one is the differences in the manufacturing process (control memory wire) used to produce the HyFlex GPF instrument, which is in agreement with previous studies (13,(28)(29)(30). In the present study, all the tested instruments have square cross sections, with the exception of the G-Files.…”
Section: Discussionsupporting
confidence: 94%
“…Unlike common fatigue tests that impose the flexure in artificial canal shapes (24), cyclic fatigue apparatus test allows a precise control over how a file is loaded during the test. This precise control can help standardizing fatigue performance testing, and predicting the fatigue lifetime of NiTi rotary instruments (23).…”
Section: Discussionmentioning
confidence: 99%
“…Se necesita un mínimo de 640 ºC para completar la transformación de martensita a austenita, esto es, para que se produzca la no deseada recristalización (22,27,31,32). De ahí que cualquier proceso de mecanizdo adicional afecte a la temperatura de transición (18,22,25,33).…”
Section: Figura 16 Comportamiento Mecánico Del Metal (23)unclassified
“…Los tipos de fractura de los instrumentos rotatorios de NiTi se clasifican en fatiga cíclica y fatiga torsional (18,19,33,35,36). La fatiga cíclica de un instrumento es aquella que ocurre como consecuencia de la alternancia de ciclos de tensión-compresión, los cuales son generados en el punto de máxima flexión del instrumento cuando rota libremente en el interior de un conducto curvo.…”
Section: 32-tipos De Fracturaunclassified
See 1 more Smart Citation